Attaining the Promise of Geminivirus-Based Vectors in Plant Genome Editing - Muhammad Arslan Mahmood; Muhammad Waseem Sajjad; Ifrah Imran; Rubab Zahra Naqvi; Imran Amin; Muhammad Shafiq; Muhammad Qasim Aslam; Shahid Mansoor (Viruses)
Over the last 40 years, several studies have provided evidence demonstrating that viral vectors can result in effective gene targeting/insertions in a host’s genome. The traditional approaches of gene knock-down, -out, or -in involve an intensive transgenesis process that is plagued by extensive timescales. Plant viruses have the potential to target specific genes and integrate exogenous DNA molecules at the target locus. Their ability to manipulate a host’s genetic material and become a part of it makes them remarkable agents and helpful for molecular and synthetic biology. In this review, we describe how geminivirus-based vectors can be utilized to overcome traditional transgenesis. We highlight the progress that has been made so far and also discuss the hurdles that hinder the employment of geminivirus-based vectors. Furthermore, we conclude with a comparison of geminivirus-based vectors with other plant-derived vectors. Geminivirus-based vectors stand poised to revolutionize plant genome editing by making nucleic acid manipulation cheaper and easier to deploy, thus lessening the major technical constraints, including homology-directed repair (HDR)-mediated genome editing and time-inefficient tissue culture procedures. The insights given in this review illustrate a broader picture of geminiviral vectors, with an emphasis on engineering plant viruses to ease genome editing practices for crop improvements as well as boost experimental timescales from years to months.